2021
DOI: 10.1111/jir.12909
|View full text |Cite
|
Sign up to set email alerts
|

Changes in physical activity across a 6‐month weight loss intervention in adolescents with intellectual and developmental disabilities

Abstract: Background Adolescents and young adults with intellectual and developmental disabilities (IDD) have high rates of obesity and low levels of physical activity. This analysis examined changes in light, moderate‐to‐vigorous physical activity (MVPA) and sedentary time, and the association between changes in MVPA and weight loss in adolescents and young adults with IDD and overweight and obesity participating in a 6‐month multi‐component weight loss intervention. Methods Adolescents and young adults with IDD and ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Although we did not use gaming software or devices in our intervention, we did include interactive games to promote behavior modification. The only other study we could find that included remote education and counseling about lifestyle behaviors through video conferencing focused on adolescents with intellectual disabilities and found no differences in outcomes for participants who received the program in-person or virtually [77,78].…”
Section: Discussionmentioning
confidence: 87%
“…Although we did not use gaming software or devices in our intervention, we did include interactive games to promote behavior modification. The only other study we could find that included remote education and counseling about lifestyle behaviors through video conferencing focused on adolescents with intellectual disabilities and found no differences in outcomes for participants who received the program in-person or virtually [77,78].…”
Section: Discussionmentioning
confidence: 87%
“…Across the three groups, MVPA at baseline was low (~15 min/day) and the change in MVPA at 6 months did not achieve statistical significance (4.5 min/day) with less than 7% of participants achieving the recommended 60 min/day of MVPA. (Ptomey et al, 2021) However, when parents were asked what they thought about the prescribed amount of physical activity for the study, most parents indicated personalised goal‐setting was helpful and motivated their adolescent to become more active. They especially liked that the health educator encouraged their adolescents to progress slowly and build physical activity into their daily routine.
…build up to it, you know we had some pretty easy goals in the beginning to make sure [adolescent] got in the mindset of tracking his steps and knowing that he needs to get on the treadmill or do whatever it is that his goal is for that week.
…”
Section: Resultsmentioning
confidence: 99%
“…Across the three groups, MVPA at baseline was low ($15 min/day) and the change in MVPA at 6 months did not achieve statistical significance (4.5 min/day) with less than 7% of participants achieving the recommended 60 min/day of MVPA (Ptomey et al, 2021). However, when parents were asked what they thought about the prescribed amount of physical activity for the study, most parents indicated personalised goal-setting was helpful and motivated their adolescent to become more active.…”
mentioning
confidence: 89%
“…Ptomey et al . (2022b) implemented a 6‐month, multi‐component weight loss intervention, which compared different diets and different modes of delivery (in‐person vs. remote) of behavioural counselling to comply with both physical activity and diet goals. Although they did achieve weight loss, which was their primary goal, physical activity did not significantly change in either of the groups and was not related to any changes in body weight in young adults with IDD.…”
mentioning
confidence: 99%